Literature Study: Analysis of Stunting Control Program Planning in Rural Areas - Dewi Agustina; Aura Dwi Rahman; Hasnah Aullia; Soleha; Nadya Elya Syahraini Br Saragih; Ami Manda Atika Putri; Indrila Sembiring; Citra Aulia Pratiwi; Chindy Aulia; Cindy Aulia Pratiwi; Layla Maznun Br Ginting; Zaskia Nabilla; Elma Riska; Mutya Purnama Ramadhani; Nadia Savira; Adinda Mulpira Br Tanjung (Universitas Muhammadiyah Palu, 2026)
Stunting is a chronic nutritional problem that is still a major challenge in Indonesia, especially in rural areas. This condition is caused by various factors such as long-term malnutrition, recurrent infections, poor sanitation, and low levels of education and family economic conditions. This study aims to analyze the planning of stunting control programs in rural areas based on literature studies from various national and international articles in the last five years. The method used is a literature study with data collection through searching scientific journals, research reports, and publications of global health organizations. Data analysis was carried out descriptively by reviewing and synthesizing various findings of previous research. The results of the study show that the main factors of stunting include maternal and child nutrition, environmental sanitation, and parenting. Specific and sensitive nutritional interventions have been proven to be effective in reducing the prevalence of stunting when carried out in an integrated manner. However, the implementation of the program still faces obstacles such as limited resources, weak cross-sector coordination, and gaps in access to health services in rural areas. In conclusion, planning an integrated, community-based, and focused stunting control program that focuses on the First 1000 Days of Life (HPK) is very important to reduce stunting rates in a sustainable manner.